High Expression of FCRLB Predicts Poor Prognosis in Patients With Colorectal Cancer - Wang, Xiaopeng; Lin, Ruirong; Zeng, Yi; Wang, Yi; Wei, Shenghong; Lin, Zhitao; Chen, Shu; Ye, Zaisheng; Chen, Luchuan (Frontiers in Genetics, 2022)
Background: Mining the prognostic biomarkers of colorectal cancer (CRC) has important clinical and scientific significance. The role of Fc receptor like B (FCRLB) in solid tumor has never been reported or studied to our knowledge. The prognostic role of FCRLB in CRC still remains to be characterized. Methods: The potential prognostic factor FCRLB was screened out through TCGA database analysis. Then its expression and associations between clinicopathological variables were assessed in TCGA CRC cohort. The prognostic value of FCRLB was assessed by multiple methods, such as Kaplan-Meier method, ROC curve, time dependent ROC analysis, and prediction model nomogram. Then, functional enrichment and annotation among the high and low FCRLB groups were achieved by GO and KEGG analysis and GSEA. Fresh CRC tissue samples obtained clinically were used for the preparation of tissue microarray and further validation. Results: FCRLB was highly expressed in CRC tissues compared to normal tissues. Meantime, over-expression of FCRLB correlated with higher CEA level, advanced T stage, N stage, M stage, AJCC stage, lymphatic invasion, perineural invasion, incomplete resection (R1 and R2 resection). Besides, high expression of FCRLB was closely correlated to less favorable OS, DSS and PFI. The analysis of CRC tissues microarray further confirmed the conclusion drawn from TCGA data analysis. Conclusion: FCRLB is notably upregulated in CRC tissues and may serves as a potential biomarker of CRC.